Review of the environmental and human health impacts of mercury use in gold mining in the Santurban Paramo area - Moreno, Daniela Garcia; Ortega-Ramirez, Angie Tatiana (International Journal of Sustainable Energy and Environmental Research, 2024)
Illegal mining is a problem that currently affects the vegetation cover of Colombia due to the environmental liabilities and the damage it causes to the environment in the eagerness to obtain gold in an easy way by using mercury. For this reason, this article presents a detailed bibliographical review of the environmental, social and economic problems of artisanal mining in the Santurban Paramo due to the inappropriate use of mercury and its impact on both the environment and the health of the people who perform this activity, describing first of all the importance of the Paramo in relation to the protection of its ecosystem and biodiversity; secondly, mercury as an imminent danger due to its use and the effects of the activity taking into account the policies and regulations carried out for the preservation and reduction of environmental contamination generated by the bad practices of artisanal mining and finally, the environmental and human health impacts due to direct and indirect contact with mercury. As a result of this research, although artisanal mining represents an important role for the survival of the community, it is necessary to implement continuous improvement strategies to reduce the use of mercury due to the problems caused by this dangerous metal both for the environment and the water source fundamental for the life of the Santurban Paramo and for the health of the people, where education and environmental awareness gain more strength for the protection and preservation of this natural reserve in Colombia.